2014
DOI: 10.5588/ijtld.14.0251
|View full text |Cite
|
Sign up to set email alerts
|

Estimated incidence of tuberculosis by capture-recapture in the Balearic Islands, 2010–2012

Abstract: The similarity of observed and estimated IR during the period 2010-2012 indicates the validity of the surveillance and the use of improved systems such as electronic medical records in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Finally, under-reporting of TB may have led to an underestimation of TB burden. Recent studies from England [25], Greece [26] and regions within Italy [27], the Netherlands [28], Romania [29] and Spain [30] have estimated under-reporting to range between 15% and 80%. One of these studies, however, found that underreporting applied less to migrants than the native population (18% vs 68%) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, under-reporting of TB may have led to an underestimation of TB burden. Recent studies from England [25], Greece [26] and regions within Italy [27], the Netherlands [28], Romania [29] and Spain [30] have estimated under-reporting to range between 15% and 80%. One of these studies, however, found that underreporting applied less to migrants than the native population (18% vs 68%) [27].…”
Section: Discussionmentioning
confidence: 99%
“…It was originally used in ecology to determine the number of animals in a specified area (3,4). Recently, these methods have widely been used to estimate incidence and prevalence of health related outcomes (5)(6)(7)(8) and to evaluate the sensitivity of surveillance or registry systems (9)(10)(11). There are four assumptions on which this method is based: first, the population should be closed that means no change should occur in the size or structure of the population during study time; second, subjects should have equal probability of being captured in given sources; third, sources should act independently that means being captured by one source should not affect the probability of being captured by other sources; and four, there must be sufficient information to make a perfect linkage among sources (2,12,13).…”
Section: Introductionmentioning
confidence: 99%